Effect of β-1, 3 glucan binding protein based zinc oxide nanoparticles supplemented diet on immune response and disease resistance in Oreochromis mossambicus against Aeromonas hydrophila. Issue 76 (May 2018) - Anjugam, Mahalingam; Vaseeharan, Baskaralingam; Iswarya, Arokiadhas; Gobi, Narayanan; Divya, Mani; Thangaraj, Merlin P.; Elumalai, Preetham
Abstract: Recently, several immunostimulants such as β-glucan, microbial and plant products have been used as dietary supplements to combat disease outbreaks in aquaculture. The present study investigates the potential of Portunus pelagicus β-1, 3 glucan binding protein based zinc oxide nanoparticles ( Pp β-GBP-ZnO NPs) supplemented diet on growth, immune response and disease resistance in Mozambique tilapia, Oreochromis mossambicus . The immune-related protein β-GBP was purified from the haemolymph of P. pelagicus using Sephadex G-100 affinity column chromatography. Pp β-GBP-ZnO NPs was physico- chemically characterized and experimental feed was formulated. Fish were separately fed with commercial diet (control-group I) and Pp β-GBP (group II, III, IV), Pp β-GBP-ZnO NPs (group V, VI, VII), chem-ZnO NPs (VIII, IX, X) mixed diet at the concentration of 0.001%, 0.002% and 0.004% respectively. Triplicate groups of O. mossambicus were fed with experimental diets twice a day for 30 days. Fish receiving Pp β-GBP-ZnO NPs supplemented diet showed a significant increase (P < 0.05) in growth performance. Cellular immune responses (myeloperoxidase activity, lysozyme activity and reactive oxygen species activity) and humoral immune responses (complement activity, antiprotease activity and alkaline phosphatase activity) were evaluated at an interval of 15 days during the feeding trial. Results demonstrate that both cellular and humoral immune responses were substantially increased (P < 0.05) in fish fed with 0.004% of Pp β-GBP-ZnO NPs supplemented diet than others. Antibiofilm potential of Pp β-GBP-ZnO NPs against Aeromonas hydrophila was visualized through confocal laser scanning microscopy (CLSM), which reveals reduction in the preformed biofilm thickness to 10 μm at the concentration of 50 μg/ml. Furthermore, after 30 days of feeding trial, fish were challenged with aquatic fish pathogen A. hydrophila (1 × 10 7 cells ml −1 ) through intraperitoneal injection. Challenge study displayed a reduced mortality rate in fish fed with diet containing Pp β-GBP-ZnO NPs. Thus our study suggests that dietary supplementation of Pp β-GBP-ZnO NPs at 0.004% may have a potential effect to enhance the immune system and survival of O. mossambicus . Graphical abstract: Image 1 Highlights: β- 1, 3 glucan binding protein based zinc oxide nanoparticles ( Pp β-GBP-ZnO NPs) were synthesized and characterized. Pp β-GBP-ZnO NPs supplemented diet actively enhances the immune response of Oreochromis mossambicus. Pp β-GBP-ZnO NPs supplemented diet fed fishes exhibit resistance against Aeromonas hydrophila infection.